(untitled) (Research, Society and Development, 2024)
Gestational Diabetes Mellitus is defined by the World Health Organization (WHO) as a pathology with the occurrence of intolerance to carbohydrates in the human body whose excess nutrients can cause high levels of glucose in the bloodstream. GDM is considered a public health problem, with a prevalence of 1 to 14% affecting pregnant women and fetuses during the gestation period. This research aims to: Raise awareness about the importance of prenatal care, and how early monitoring helps to diagnose possible complications caused by Gestational Diabetes during pregnancy. Methodology: research envolvesse a Bibliographic Review, with a qualitative, descriptive approach, developed through scientific articles and magazines. Results: 36 journals were initially selected and after reading the abstracts, 16 journals were discarded, leaving 20 journals to make up the selection. Final Considerations: The study identified how much Gestational Diabetes brings complications to women and the fetus, making it necessary for prenatal care to be provided early, by a nursing professional, who aims to contribute through guidance and clarification of doubts, seeking early diagnosis of various pathologies, and being directly at the forefront of preventing and treating gestational Diabetes through women’s health policies.